The Innovation of Eco-Friendly Energy Corn Cob Briquettes as Agricultural Waste Reduction in Wangun Hamlet, Sugio - Agustin, Elsa Putri; Nadifah, Wilda Izza; Kahfi, Mas’ady Ashabul; Putra, Agil Heedyono; Syaharin, Aura Rismayani; Sulhi, Cindy Himayatus; Firdausi, Fina Nahwa; Nabil, M. Rafi Shalahuddin (Jurnal Serambi Abdimas, 2025)
Corn cobs are one type of agricultural waste that is abundant but has not been optimally utilized in rural areas. In Wangun Hamlet, Daliwangun Village, Sugio Subdistrict, corn cobs tend to be discarded or only used as fuel. The lack of understanding and awareness among the community is the main reason why this waste is not managed productively. The Community Service Learning (CSL) program for students at UIN Sunan Ampel Surabaya addresses this issue through training on the utilization of corn cobs into environmentally friendly briquettes. This study employs the Participatory Action Research (PAR) method and descriptive qualitative methods to describe the training process, evaluate its impact on community knowledge, and assess the program's sustainability potential. The results of the activity showed an increase in residents' understanding of the value of agricultural waste and high enthusiasm for participating in briquette-making practices. Support from the village head, village stakeholders, Karang Taruna, and the mosque youth group strengthened the program's sustainability and its integration into the Village-Owned Enterprise (BUMDES). These findings indicate that processing agricultural waste through an approach that actively involves various segments of the community not only impacts environmental cleanliness but also opens new opportunities for village economic empowerment. This research is expected to serve as a model for the development of alternative energy and community-based waste management in other agricultural areas with similar potential.